Factors Influencing BPJS Patients' Lack of Understanding of the Outpatient Referral System - Fitria, Dilla; Sulisna, Aida; Dermawan, Rizka Putri (Hasanuddin Medan, 2024)
Introduction: Referrals are carried out based on medical indications so that community health centers and their networks can filter referrals. The problem that occurs in patients' understanding of referral services is that socialization to the community is still very limited. The results of interviews with 10 outpatients at the UPT Puskesmas Sawit Seberang showed that 6 patients (60%) still did not understand the referral criteria, while the other 4 patients (40%) clearly understood the outpatient referral system. Objective; to determine the factors that influence BPJS patients' lack of understanding of the outpatient referral system at the Sawit Seberang Community Health Center UPT, Langkat Regency. Methods: This type of research is quantitative using an analytical survey design with a cross-sectional approach. The research population was all 781 BPJS patients with a sample of 89 people taken using accidental sampling technique. Data analysis used univariate, bivariate analysis with the chi-square statistical test and multivariate analysis with the logistic regression test. Results: The results of the research show that the p value for the knowledge variable is p = 0.020, attitude p = 0.017, information p = 0.012 and health workers p = 0.025, which means that there is an influence of knowledge, attitudes, information and health workers on BPJS patients' understanding of the outpatient referral system. Conclusion: The research conclusion is that there is an influence of knowledge, attitudes, information and health workers on BPJS patients' understanding of the outpatient referral system at the UPT Puskesmas Sawit Seberang, Langkat Regency.